Mass spectrometry - McCloskey, J. A. (James A.) (Methods in enzymology ;, 1990)
This volume presents a compilation of experimental methods and principles, with detailed protocols and examples. Techniques which have demonstrated value in problem-solving are included. Intended for biochemists, cell biologists, microbiologists, pharmacologists, biomedical scientists, biophysicists, analytical chemists, and physiologists, this book focuses on mass spectrometry. Topics discussed include the methods of ionization, liquid chromatography, continuous flow fast atom bombardment mass spectrometry, collision-induced dissociation, enzymatic and chemical digestion of proteins, and constituents of nucleic acids. Other titles in this series include Guide to Yeast Genetics and Molecular Biology and Retinoids, Part B: Cell Differentiation and Clinical Applications.